Determinants of Sukuk rating: empirical analysis of asset-based and asset-backed Sukuk - Omar, Mohd. Azmi (s.n, 2013)
The development of Sukuk market as the alternative to the existing conventional bond market has risen the issue of rating the Sukuk issuance. These credit rating fulfil a key function of information transmission in capital market. Moreover, basel Committee for Banking Supervision has now instituted capital charges for credit risk based on credit ratings